(untitled) (Altre Modernità, 2020)
This text, reissued after the first publication in the catalogue of Beppe Devalle’s solo exhibition at MART (Rovigo), describes and explains a specific turning point in the painter’s artistic choices that opened in 1993, when – according to the critic and in a way testified by the expressive choices of those years – a previously unaccounted for violence broke out in Devalle’s production. With the perceptiveness that derives from a profound competence combined with the ability to read Devalle’s works in an articulate and complete way, Trento includes the pictorial fact into a revealing social and cultural framework, which helps quite a bit to understand the artistic choices and the impact of Devalle’s works.